IDIOMS IN ENGLISH AND UZBEK CULTURES: TRANSLATION AND APPLICATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article aims to analyze idioms in English and Uzbek cultures, focusing on their translation and application. Idioms are an integral part of language, reflecting cultural characteristics. The article discusses the challenges encountered during the translation of English and Uzbek idioms and suggests methods to overcome these issues. Additionally, it presents examples of common idioms in both cultures, explaining their meanings and usage. The article provides practical recommendations for translators and linguists.